201 Human oxidised phospholipid macrophages have high lipoprotein handling capabilities without readily forming unwanted foam cells. (5th June 2017) - Baidzajevas, Kajus; Hadadi, Eva; Lee, Bernett; Lum, Josephine; Sudbery, Ian; Lai, Sarah; Wong, Siew Cheng; Kiss-Toth, Endre; Wilson, Heather
Abstract : Rationale: Cardiovascular disease is the leading cause of death world–wide. Macrophages are crucial in regulating the plaque environment, especially the lipid content. However, current characterisation of macrophage phenotypes lipoprotein handling capacity is conflicting and incomplete. We hypothesised that lipoprotein handling differed among distinct macrophage phenotypes due to differential gene and protein expression. We tested this using a range of functional, gene and protein expression assays. Methodology: Monocytes were isolated from healthy donor blood by gradient centrifugation and magnetic selection, then differentiated into macrophages over 7 days using M–CSF. Macrophages were polarised over 24 hour by IFNγ+LPS, IL–4, IL–10, oxPAPC (oxidised phospholipid) and CXCL4, respectively. Unpolarised macrophages were used as controls. Foam cell formation was determined by Oil–Red–O staining and acLDL uptake was detected by flow cytometry. Cholesterol content and efflux were measured using colorimetric and fluorescent assays. RNA expression was determined by RNA-seq and qRT-PCR and cell surface protein expression was measured by flow cytometry. Results: IFNÃ&noentity;Â³+LPS macrophages did not readily form foam cells (0.23 compared to unpolarised) or process lipoprotein particles, whereas IL–4 and IL–10 polarised macrophages displayed the highest capacity in foam cell formation (1.02 and 1.08 compared to unpolarised) and lipoprotein handling. OxPAPC macrophages exhibited lipoprotein processing capabilities similar to IL–4 and IL–10 macrophages, but did not readily form foam cells (0.22 compared to unpolarised). CXCL4 macrophages displayed intermediate foam cell formation (0.84 compared to unpolarised) and lipoprotein handling capabilities. Differences in foam cell formation and lipoprotein uptake correlated directly to specific scavenger receptor gene and protein expression. Only IFNγ+LPS macrophages had significantly reduced expression of key internal lipoprotein processing genes (q 0.0001). Cholesterol efflux correlated directly to specific ABC transporter protein, but not RNA expression. Conclusions: In vitro human macrophage phenotypes differ in foam cell formation and lipoprotein handling capabilities that are associated with differential key gene and protein expression.